Aux sources démocratiques du malaise dans la temporalité - Paul Zawadzki (Temporalités)
In a very extensive bibliography today, much of the analysis of the malaise in temporality focuses on the exploration of the effects of capitalism and industrial society. The experience of individuals is then described from the standpoint of alienation and dispossession. However enlightening and fruitful this approach may be, it leaves aside the analysis of the logic of detemporalization that emerged from within the democratic universe itself, which some classics (notably Tocqueville) had intuited. This article aims to reintegrate the intelligibility of the crisis of temporality, as it was understood by the human and social sciences mainly in the 1970s and 1980s within the framework of a theory of democracy, mainly borrowed here from the philosophical history proposed by Marcel Gauchet. The perspective introduced here makes it possible to think of the very paradoxical concomitance in the 1970s and 1980s of a feeling of dispossession of temporality at the very moment of the triumph of the democratic principle in Western societies.